Burnout and distress in Australian physician trainees: Evaluation of a wellbeing workshop. (June 2019) - Axisa, Carmen; Nash, Louise; Kelly, Patrick; Willcock, Simon
Objective: To evaluate the effectiveness of a workshop intervention to promote wellbeing for Australian physician trainees using a randomized-controlled design. Methods: Participants were randomly assigned into intervention and control groups. The intervention group attended a half-day workshop. Outcome measures included depression anxiety stress scale, professional quality of life scale and alcohol use disorders identification test. Demographic and work/life factors were measured. Measurements were recorded at baseline, 3 and 6 months, and the workshop was evaluated by participants. Results: High rates of burnout (76%) and secondary traumatic stress (91%) were detected among study participants and around half met screening criteria for depression (52%), anxiety (46%) and stress (50%) at baseline. Workshop evaluations showed that participants agreed that the training was relevant to their needs (96%) and met their expectations (92%). There was a small reduction in alcohol use, depression and burnout in the intervention group compared with the control group at 6 months, but these changes did not reach statistical significance. Conclusion: High rates of psychological morbidity detected in the study suggest that physician trainees are a vulnerable group who may benefit from initiatives that promote wellbeing and changes in the workplace to reduce distress.